Influence of phenoxy addition on the curing kinetics for uncatalyzed and catalized cyanate ester resin - Remiro, Pedro M. (2010)
The curing behavior of the dicyanate ester of bisphenol-A (DCBA) modified with poly(hydroxy ether of bisphenol-A) (phenoxy) is studied by differential scanning calorimetry in dynamic and isothermal tests at temperatures between 120 and 240°C. The addition of phenoxy to DCBA produces an increase in the reaction rate and a decrease in the temperature of maximum reaction rate for the uncatalyzed resin, and also for the system catalyzed with copper (II) acetyl acetonate/nonylphenol. The exothermic heat of curing for the mixtures is also dependent on the phenoxy content. These facts evidence a catalytic effect of phenoxy on the curing of the cyanate ester resin, even though an autocatalytic behavior is observed for all uncatalyzed DCBA/phenoxy mixtures. A simplified mechanistic kinetic model is used to calculate the kinetic parameters. For the uncatalyzed systems, a decrease in the kinetic constant for the initiation reactions, and an increase in the propagation constant are measured when the cyanate content increases. The thermal activation energy for the initiation reaction of the catalyzed systems is lower than that of the uncatalyzed ones, and it depends on the weight fraction of cyanate in the mixture.